Expression of H2S in Gestational Diabetes Mellitus and Correlation Analysis with Inflammatory Markers IL-6 and TNF-α. (23rd March 2020) - Teng, Yucui; Xuan, Shuxia; Jiang, Ming; Tian, Li; Tian, Jinjing; Chang, Qian
Abstract : Background . Gestational diabetes mellitus (GDM) is a severe threat to the health of both mother and child. The pathogenesis of GDM remains unclear, although much research has found that the levels of hydrogen sulfide (H2 S) play an important role in complications of pregnancy. Methods . We collected venous blood samples from parturient women and umbilical vein blood (UVB) and peripheral venous blood (PVB) samples one hour after childbirth in the control, GDM-, and GDM+ groups in order to determine the concentration of glucose and H2 S in plasma; to measure levels of TNF- α, IL-1 β, IL-6, TGF- β 1, and ADP in parturient women and the UVB of newborns; and to find the correlation of H2 S with regression. Results . We found that, with the elevation of glucose, the level of H2 S was decreased in GDM pregnant women and newborns and the concentrations of IL-6 and TNF- α were upregulated. With regression, IL-6 and TNF- α concentrations were positively correlated with the level of blood glucose and negatively correlated with H2 S concentration. Conclusion . This study shows that downregulation of H2 S participates in the pathogenesis of GDM and is of great significance in understanding the difference of H2 S between normal and GDM pregnant women and newborns. This study suggests that IL-6 and TNF- α are correlated with gestational diabetes mellitus. The current study expands the knowledge base regarding H2 S and provides new avenues for exploring further the pathogenesis of GDM.